الشیخ طه جابر العلواني وجهوده الفكریة - عدائكة, راضية; رمضاني, راضية; بوهني, نصيرة; زغوان, مريم; تواتي طليبة, سعيدة (جامعة الوادي university of eloued, 2019)
تناول هذا البحث الجهود الفكریة لطه جابر العلواني وأیضا قمنا بد ا رسة حیاة طه جابر العلواني، وقد جاء كل هذا في ثلاثة مباحث كان أولها سیرته الذاتیة وحیاته العلمیة والعملیة وآثاره، بینما المبحث الثاني فقد تضمن الجهود الفكریة لطه جابر العلواني في المجال الدیني تمثلت في الد ا رسات القرآنیة والعقیدة والشریعة والأخلاق، أما المبحث الثالث والأخیر فتضمن أیضا الجهود الفكریة لطه جابر العلواني في مجالات أخرى سیاسیا واجتماعیا وفلسفیا. Study Summary This research dealt with the intellectual efforts of Taha Jabir Al-Alwani, and we also studied the life of Taha Jaber Al-Alwani. All of this came in three fields: the first was his biography, his scientific and practical life and his effects; the second was the intellectual efforts of Taha Jaber Al-Alwani in the religious field, Sharia and ethics. The third and final topic also includes the intellectual efforts of Taha Jabir al-Alwani in other areas, politically, socially and philosophically.
دعوة